Development of software systems for the design of technically complex products - Martyanov, E I; Malygin, E N (Journal of physics. Conference series, 2021)
In the article, we propose the algorithm of development of program system which can be applied to designing technically complex products for the mathematical description of which the systems of differential equations with partial derivatives are used. This system allows us to obtain more accurate results than engineering methods and is relatively easy to use. As an example of implementing the proposed algorithm, we have created a subject-oriented software system designed to solve the problem of determining a two-blade stirrer’s design parameters and operating characteristics.